PERANCANGAN ALAT PENYIRAMAN TANAMAN KRISAN OTOMATIS MENGGUNAKAN NODEMCU BERBASIS INTERNET OF THINGS (IOT) (STUDI KASUS : RIKI FLORA) - Endah Sumiati; Bambang Santoso (CV. Multi Kreasi Media, 2023)
The development of knowledge and technology today encourages people to continue to think more creatively, not only exploring new discoveries, but also maximizing the performance of existing technology and continuing to innovate to ease human work in everyday life. The field of knowledge and technology is developing very rapidly, therefore we must be able to compete and master technology. Cultivating ornamental plants and fruit trees is a promising business. However, it is not easy to maintain. Like humans, plants need water for growth and development. Plants should not lack or excess water, soil that lacks water makes plants grow slowly and in ornamental plants makes plants look not fresh and wilted and vice versa, plants that have too much water also make plants unhealthy and can even cause plants to die. In watering plants, the owner usually does not pay attention to the conditions and needs of the plant. This causes plants not to get water intake that is in accordance with the needs of the plant itself. For this reason, this final project aims to make a plant watering device automatically by paying attention to soil moisture levels. By using a soil moisture sensor that functions as a reader of soil moisture levels. Then use a relay that functions to turn off and turn on the water pump. The ESP8266 module is also used as a data sender to the web which produces a display of sensor reading data results.